Retracted: miR‐30d‐5p suppresses proliferation and autophagy by targeting ATG5 in renal cell carcinoma - Liang, Liang; Yang, Zheng; Deng, Qian; Jiang, Yazhuo; Cheng, Yongyi; Sun, Yi; Li, Lei (FEBS open bio, 2021)
Previous reports have shown that miR‐30d‐5p functions as a tumor suppressor in prostate cancer and gallbladder carcinoma, but its role in renal cell carcinoma (RCC) remains elusive. This study was designed to explore the functional role of miR‐30d‐5p in proliferation and autophagy of RCC. Our results show that miR‐30d‐5p is significantly down‐regulated in RCC tissues compared with normal tissues. miR‐30d‐5p overexpression suppressed cell proliferation, cell‐cycle G1/S transition and autophagy, but promoted apoptosis in RCC cell lines (786‐O and ACHN). Intriguingly, autophagy‐related gene 5 (ATG5) was directly targeted by miR‐30d‐5p, as shown using luciferase reporter assay and biotin‐avidin pull‐down assay. Moreover, overexpression of ATG5 attenuated the inhibitory effect of miR‐30d‐5p on proliferation and autophagy in 786‐O cells. These results suggest that miR‐30d‐5p suppresses proliferation and autophagy in RCC cells by targeting ATG5, and this pathway may be a suitable basis for the design of novel cancer therapeutics.